Spatial indicators of inequity in urban health research: a scoping review - Ana L. Favarão Leão; Raúl D. Gierbolini-Rivera; Milena Franco Silva; Courtney Shaw; Áine O’Connor; Deborah Salvo; Rodrigo Siqueira Reis (Discover Public Health)
Abstract Accurately measuring spatial inequities in the built environment is essential for meaningful research on how environmental factors influence health. This study aimed to (1) systematically identify how spatial inequities are measured in urban health research and (2) assess the conceptual clarity of studies on spatial inequities and inequalities. A scoping review of four electronic databases (PubMed, Web of Science, GreenFILE, and Global Health) was conducted. From 921 results, 44 full-text articles were reviewed. Studies most frequently measured access to green spaces (n = 20, 45.5%), food environment (n = 7, 15.9%), and walkability (n = 5, 11.4%). Most studies (n = 32, 73%) were conducted in high-income countries. The primary analytical approaches were descriptive (n = 11, 25%). Most studies (n = 43, 97.73%) contained misalignment between concepts they purposed to measure, and variables and analyses used. Concepts such as accessibility (n = 10, 22.72%), environmental justice (n = 5, 11.36%), and spatial equity (n = 3, 6.81%) were prevalent. This study’s results highlight the need for conceptual clarity on spatial inequity and inequality within urban health research. This research highlights the reliance on descriptive methodologies and advocates for robust statistical approaches. With conceptual clarity and improved measurements, researchers and practitioners can better develop strategies to advance urban health policies with the goal of reducing health inequities.